Chemical Study of the Seeds of Dolichos biflorus - Dubey, K.S.; Ansari, A.H. (Asian Journal of Chemistry, 2010)
Chemical study of the seeds of Dolichos biflorus has been made. Varioussugars and amino acids were separated and identified using moderntechniques.